RESISTÊNCIA DE CULTIVARES TRANSGÊNICAS DE SOJA À Bemisia tabaci BIÓTIPO B - DA CUNHA, Júlia Souza Pires; TOSCANO, Luciana Cláudia; DEZAN, Iris Mendes Namizaki; COCCO, Andrezza Santos; TENÓRIO, Kamila de Paula; NOGUEIRA, Lavínia Rodrigues (ANAIS DO ENIC, 2025)
-